Improved diagnostic performance of CASPAR criteria with integration of ultrasound - Geng, Yan; Song, Zhibo; Zhang, Xiaohui; Deng, Xuerong; Wang, Yu; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background The difficulty in determining synovitis, tenosynovitis, or enthesitis by physical examination (PE) has limited the diagnostic capability of CASPAR for psoriatic arthritis (PsA). Therefore, we aimed to evaluate the diagnostic utility of CASPAR with the integration of ultrasound (US). Methods Patients with a hint of PsA were enrolled. Besides routine PE for tender or swollen joints, enthesitis, and dactylitis, US was performed to evaluate peripheral joints, entheses, and tendons. The additional value of the US to the CASPAR criteria was analyzed. Results A total of 326 consecutive patients with 164 PsA and 162 non-PsA were enrolled. A total of 162 non-PsA patients consisted of 58 cases of psoriasis (PsO), 27 osteoarthritis with PsO/family history of PsO, five fibromyalgia with PsO, 69 sero-negative rheumatoid arthritis, and three undifferentiated arthritis. Significantly higher frequencies of tenosynovitis and enthesitis on US and new bone formation on X-rays were found in PsA vs. non-PsA patients (59.1% vs. 13.0%; 63.4% vs. 14.2%; 62.2% vs. 8.0%, p <0.01 for all). Logistic regression analysis showed that dactylitis (OR = 12.0, p <0.01), family history of PsO/PsA (OR = 3.1, p <0.05), nail involvement (OR = 3.5, p = 0.01), new bone formation on X-ray (OR = 14.8, p <0.01), tenosynovitis on US (OR = 21.3, p <0.01), and enthesitis on US (OR = 21.7, p <0.01) were independent risk factors for PsA. By combining US tenosynovitis and/or enthesitis, the diagnostic utility of CASPAR criteria was improved, with superior specificity (91.4% vs. 84.0%) and similar sensitivity (95.7% vs. 94.5%). Replacing X-ray by US or adding US, the CASPAR criteria showed comparable sensitivity and specificity for PsA diagnosis. The diagnostic accuracy was 89.3% for CASPAR criteria based on PE, 93.6% for CASPAR added with US, and 93.3% for CASPAR with US replacing X-ray. Conclusion The diagnostic utility of the CASPAR was improved by integrating tenosynovitis and/or enthesitis when using US. US provides additional value for PsA recognition.